Pengaruh Bauran Pemasaran dan Kearifan Lokal Terhadap Minat Berkunjung Wisatawan di Pulau Pramuka - Ahmad, Abdullah Ghani; Mustika, Amalia; Ratu Bilqis, Linda Desafitri (Jurnal Pariwisata, Bisnis dan Digital; Vol 2 No 2 (2026): Jurnal Pariwisata, Bisnis dan DigitalDO - 10.30647/jpbd.v2i2.2099, 2026)
Pramuka Island has marine tourism potential in the form of beautiful coral reefs which can be enjoyed with various activities such as snorkeling and diving. One of the efforts that can be made by the management or local community is to carry out a marketing mix to introduce the potential and local wisdom of Pramuka Island so that it can attract visiting tourists. This research uses a research approach, namely quantitative descriptive, with the testing method used is Purposive Sampling, namely by taking a sample of 100 respondents from tourists who have visited and are currently visiting Pramuka Island, and data is also obtained from the results of the researcher's direct observations on Pramuka Island. The research data were analyzed using Multiple Linear Regression tests and Hypothesis tests as well as research instruments using a Likert Scale Model with a value of 1 – 5. The results of the research after conducting regression tests and hypothesis tests, showed that the marketing mix and local wisdom together (simultaneously) had a relationship and influence on interest in visiting Pramuka Island, namely 65.3%. Meanwhile, partially the marketing mix has a significant influence on tourists' interest in visiting with a t-count value (7.498) > t-table (1.985), and local wisdom also has a significant influence on tourists' visiting interest with a t-count value (2.803) > T-table (1,985). Keywords : marketing mix, lokal wisdom, interest in visiting, Pramuka Island